Kompensasi Terhadaap Anak Sebagai Korban Tindak Pidana Perkosaan - Larwuy, Weny Yorinike; Adam, Sherly; Salamor, Yonna Beatrix (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2023)
Introduction:Protection for victims of criminal acts can be interpreted as protection to obtain guarantees or legal compensation for the suffering or losses of victims of criminal acts so that they are paid more attention to by the State, one of which is the victims of rape crimes because victims are entitled to compensation provided by the State.Purposes of the Research:This study aims to review and discuss the Mechanism for Providing Compensation to children victims of the Rape Crime and the reasons for the judge so that in his decision compensation for children is handed over to the State treasury.Methods of the Research:The type of research used in this writing is nomative juridical. The problem approach used is the Statutory approach, the conceptual approach and the case approach. Legal materials used primary legal materials and secondary legal materials. The technique of collecting legal materials is carried out by means of literature studies. The management and analysis of materials is analyzed qualitatively.Results of the Research:Based on the results of the study, the compensation mechanism is regulated in Government Regulation No. 44 of 2008 concerning the Provision of Compensation, Restitution, and Legal Assistance to Witnesses and Victims. Compensation must be filed prior to a court decision that does not yet have permanent legal force. The Witness and Victim Protection Agency (LPSK) may apply for compensation to the public prosecutor to be included in criminal prosecutions because the compensation application must be submitted by the victim or the victim's family or their attorneys through the Witness and Victim Protection Agency (LPSK). The judge in his ruling so that the compensation of the child as a victim of the crime of rape is handed over to the State treasury because the child as a victim of a criminal act does not apply for compensation through the Witness and Victim Protection Agency to the Public Prosecutor and proceed to the Court so that in the judgment the rights of the child victim of the rape crime is handed over to the treasury.